Multistep kinetic study of Fe2O3 reduction by H2 based on isothermal thermogravimetric analysis data deconvolution. (22nd May 2023) - Wang, Haiming; Liu, Bingjie; Yang, Guangyao; You, Changfu
Abstract: The multistep kinetics of Fe2 O3 reduction by H2 is investigated by data deconvolution in this study. The reduction process was conducted in a TGA apparatus isothermally in the temperature range of 750–950 °C. The stepwise reduction of Fe2 O3, i.e. Fe2 O3 –Fe3 O4, Fe3 O4 –FeO, and FeO–Fe, was successfully decoupled from each other without controlling the reduction gas atmosphere. The overlapping, as well as the reaction rate, of each reduction step can be described by the deconvoluted data with R 2  > 0.995 for all the tested temperatures. Based on the deconvolution, relatively stable activation energy with increasing the conversion was obtained for each step with the model-free iso-conversion method, indicating the rationality of the decoupled multistep profiles. Master plot was then applied to evaluate the suitability of kinetic models reported in the open literature. The JMA model (Avrami-Erofe'ev equation), corresponding to the nucleation and growth mechanism, was found to be most suitable for describing each reduction step. The activation energies obtained by the JMA model fitting for Fe2 O3 –Fe3 O4, Fe3 O4 –FeO, and FeO–Fe were 10.3, 26.7, and 24.8 kJ/mol, respectively, which also agree well with the Ea obtained by the model-free method. Highlights: Mathematic deconvolution was used to decouple the stepwise reduction of Fe2 O3 by H2 . The phase transformation at different reduction extents was identified experimentally. Activation energy was obtained for each step based on the deconvoluted TGA profile. Nucleation and growth model was most suitable for describing the reduction process.